Crime in Culture: Analysis of the Sarong War in the Holy Month from a Criminal Law Perspective - Isnawan, Fuadi (Journal Equity of Law and Governance, 2024)
The phenomenon of crimes committed by teenagers is growing day by day. These crimes can be led by various factors which make them vent their emotions to other people or groups. One of the phenomena that occurred in the holy month of Ramadan is the phenomenon of sarong wars, which used to be a tradition that has now turned into something motivated by emotions because of mutual challenges on social media victimized by teenagers. This phenomenon is a surprising thing because in the holy month where they should worship a lot, they instead commit various kinds of crimes, namely the sarong war. This research focuses on how the responsibility of teenagers involved in the sarong war is what efforts are made by the police to prevent the phenomenon of the sarong war. This research is conducted in a normative juridical method that will examine the research topic which will be processed by using various kinds of relevant reference sources to obtain a deep understanding of the topics and problems studied in this study. One result obtained from this research is that adolescents have the ability to be responsible in the criminal act because they do not have psychiatric disorders that have been included in the law. So that those involved can be subject to strict sanctions. Efforts made by the police are to conduct patrols to prevent the sarong war, which is physical and cyber.